EFFECT OF FLY ASH ON PRODUCTS OF WATER HYACINTH CATALYTIC PYROLYSIS - Rinna Juwita; Jefriadi Jefriadi; Khairunnisa Aprilianti; Mitha Amalia; Rinny Jelita (Universitas Lambung Mangkurat, 2022)
The use of alternative energy is needed to overcome the availability of fossil energy sources. One alternative energy source is water hyacinth through a pyrolysis process using a catalyst. Fly ash has the potential to be a catalyst given its very low utilization in Indonesia. Utilization of water hyacinth biomass through a pyrolysis process using a fly ash catalyst was carried out to determine the effect of catalyst activation and the amount of the catalyst on the pyrolysis product. The purpose of this study was to determine the optimum amount of catalyst and the effect of catalyst activation on water hyacinth pyrolysis products. The experiment was carried out in an electric pyrolysis reactor equipped with a condenser as a coolant and a thermocouple. Nitrogen gas is fed into the pyrolysis reactor to create inert conditions that prevent sample burning. The crushed water hyacinth samples were put into the reactor with the fly ash catalyst with a catalyst composition of 0%, 5%, 10%, and 15% of the raw material. The process lasted for 1 hour at 500 oC. The liquid product in the form of bio-oil is collected and then its mass and volume are measured. The solid product in the form of charcoal is taken after the pyrolysis process is complete and the reactor reaches room temperature and then its mass is measured. The highest liquid and solid yields were obtained with 10% activated catalyst variations, namely 39.142% for liquids and 45.144% for solids.